Guidance provision for the bright children of Francisco Benitez Elementary School - Galvan, Violeta R. 1930- (1967)
The aim of the study is to present existing guidance services provided at the Benitez Elementary School, one of the public elementary schools in Manila. It attempts to present guidance provisions for the bright as a part of the regular guidance program of the school. The seminar paper suggests ways and means of adequately meeting the guidance needs of bright children.